Prevalence of Ishihara Test Failures in a Large Cohort of Military Conscripts - Sturm, Veit; Jaggi, Gregor; Todorova, Margarita G.; Messerli, Jürg; Zawinka, Claudia; Eppenberger, Leila Sara (Klinische Monatsblätter für Augenheilkunde, 2025)
Purpose Color vision deficiency (CVD) is a common vision disorder. It is predominantly caused by inherited photopigment abnormalities in the retina. The absolute number of cases with CVD is expected to increase worldwide with the growing population.Methods Data from male military conscripts for the recruitment period of 2008 to 2017 were retrospectively analyzed. Year of recruitment, conscriptsʼ birth year, visual acuity, refractive status (spherical equivalent), and color vision status (normal Ishihara pseudoisochromatic plates test yes/no) were available.Results The dataset comprised data on a total of 355 657 male conscripts who had undergone recruitment between the years 2008 to 2017. The mean number of conscripts per year was 35 566 (MD = 35 440, SD = 1 249), reaching a minimum count of 33 998 conscripts in 2017 and a maximum of 37 594 in 2011. The mean age at recruitment was 19.7 years (MD = 19.0 y, SD = 1.1 y). Among the conscripts, 337 422 (94.9%) successfully passed the Ishihara test, while 18 235 (5.1%) were found to have CVD.Conclusion The overall prevalence of CVD in our male cohort was 5.1%. This figure is slightly lower than that reported for a European Caucasian population.
Keywords: Europe; color vision deficiency; military conscripts; Swiss military